Encouraging Visits to Geoparks through Sustainable Marketing: A Conceptual Study on Geopark Dieng - Doni Sugianto, Sihotang; Usep, Suhud; Agung Wahyu, Handaru
Geopark tourism plays a crucial role in sustainable tourism by promoting visitor attractions while emphasizing the conservation of geological heritage, public education, and the empowerment of local communities. However, scholarly focus on the factors influencing visit intentions in geopark contexts, particularly from a sustainable marketing perspective, is limited. This conceptual paper presents a theoretical framework illustrating how publicity, destination attributes, and word of mouth (WOM) contribute to the formation of destination awareness, destination image, and destination preference, ultimately shaping visit intentions. Drawing from tourism marketing literature and consumer behavior theories, the study proposes twelve research propositions. Destination awareness and destination image serve as key psychological mechanisms that mediate the effects of external factors on destination preference and visit intention. Publicity enhances awareness and strengthens image through credible exposure, while destination attributes, such as accessibility, attractiveness, and amenities, impact both preference and image. Additionally, WOM lends authenticity and trust, further reinforcing awareness and perception. The model highlights destination preference as the vital link between perceptions and tourists’ intentions to visit. Theoretically, this paper enriches the sustainable tourism literature by extending destination marketing concepts to geopark tourism. Practically, it provides insights for geopark managers to develop sustainable marketing strategies through credible publicity, effective management of sustainable attributes, and WOM-based experiential promotion. Although conceptual, this framework paves the way for empirical research, including tests across various forms of special interest tourism and the incorporation of cultural distance or behavioral theories to connect revisit intentions with actual behavior.